An Analysis of Maxim Gorky’s Short Story Her Lover - Gunes, Ali (Journal of History Culture and Art Research, 2013)
This paper debates three views in Maxim Gorky’s short story Her Lover. The first one is human loneliness, lack of communication, fragmented and lost identity in modern industrialized Russian society, which was actually a general view in the early decades of the twentieth century. Secondly, Gorky endows his fictional character Teresa with the Romantic energy which enables her to survive her misery and loneliness by inventing an imaginary lover. Finally, the paper examines the views of prejudice and self-sufficiency which put serious hurdles before real communication and thus cause the spiritual and moral decay in social life and relationships.